Actuator disk methods for tidal turbine arrays - Hunter, W (2015)
Tidal stream energy presents challenges that will require the development of new engineering tools if designs are to harness this energy source effectively. At first glance one might imagine that tidal stream energy can be treated as wind with appropriate adjustment for fluid properties of water over air, and account taken of the harsher offshore environment; both waves and turbulence. However, it is now well accepted that the flow past turbines that are constrained by the local sea bed, sea surface, and possibly also neighbouring turbines and channel sides, will differ markedly from that of an ostensibly unblocked wind turbine. Garrett & Cummins (2007) were the first to demonstrate that operating a turbine in a non- negligibly blocked flow passage presents a different flow solution and importantly a significant opportunity to enhance the power that can be delivered by blocked turbines with the limit of power extraction exceeding the Lanchester-Betz limit for operation of unblocked wind turbines. Although it is impractical to array real turbines across the entire width of a channel it has been proposed to use short arrays of turbines making use of local constructive interference (blockage) effects; Nishino & Willden (2012) showed that although the phenomenal power limits of Garrett & Cummins are unobtainable in a real flow, a significant uplift in the limit of power extraction can be achieved for short fences of turbines arrayed normally to the flow in wide cross-section channels. However, it does not follow that rotors designed using unblocked wind turbine tools are capable of extracting any more power than they are designed for and hence the power uplift made available through blockage effects may be squandered. This thesis sets out to develop design tools to assist in the design of rotors in blocked environments that are designed to make use of the flow confinement effects and yield rotors capable of extracting some of the additional power on offer in blocked flow conditions. It is the pressure recovery condition used in wind turbine design that requires relaxation in blocked flow conditions and hence it is necessary to resort to a computational framework in which the free stream pressure drop can be properly accounted for. The tool of choice is a computational fluid dynamics embedded blade element method. As with all models with semi-empirical content it is necessary to select and test correction models that account for various simplifications inherent to the use of the blade element method over a fully blade resolved simulation. The thesis presents a rigorous comparison of the computational model with experimental data with the various correction methods employed. The tool is then used to design rotors, first for unblocked operation, with favourable comparison drawn to lifting line derived optimal Betz rotor solutions. The final objective of the study is to design rotors for operation in short fence configurations of four turbines arrayed normally to the flow. This is accomplished and it is shown that by using bespoke in situ rotor design it is possible to extract more power than possible with non-blockage designs. For the defined array layout and operating conditions, the bespoke rotor array design yields a power coefficient 26% greater than the implied Betz limit for an unblocked rotor and 4% greater than operating a rotor designed in isolation in the same array.